Rol de la mujer profesional en los medios impresos durante la década de los ochenta en el ámbito guayaquileño - Silva Ricaurte, Danna Paola (2021)
In Ecuador there are various mass media, but without a doubt those of an audiovisual nature such as television are those that stand out most in Ecuadorian society. On the other hand, historically, the role of women in these media has been loaded with stereotypes that have avoided their role in the illustration of sexuality and marketing. That is why the present research work sought to explore the role of professional women in the visual media to determine the dynamics of the same in the same, seeing what aspects are prioritized, the positions designated in the different television channels and main activities performed….....